Radiation therapists’ perceptions of thermoplastic mask use for head and neck cancer patients undergoing radiotherapy at Ocean Road Cancer Institute in Tanzania: A qualitative study - Furahini Yoram; Nazima Dharsee; Dickson Ally Mkoka; Khamza Maunda; Jumaa Dachi Kisukari (PLoS ONE, 2023)
Introduction A thermoplastic mask is the most widely used immobilization device for head and neck cancer patients undergoing radiotherapy. The radiation therapist is the staff responsible to prepare these masks and set-up the patients for treatment, a procedure that requires time, patience, and precision. An understanding of Radiation therapists’ perceptions regarding thermoplastic mask use will help design interventions to address challenges encountered in its use. This study explored Radiation therapists’ perceptions of thermoplastic mask use for head and neck cancer patients undergoing radiotherapy at Ocean Road Cancer Institute in Tanzania. Material and methods An exploratory qualitative study design was used to explore thermoplastic mask use for head and neck cancer patients undergoing radiotherapy. Semi-structured in-depth interviews were conducted, involving fifteen Radiation therapists from Ocean Road Cancer Institute in Tanzania between March and May 2021. A thematic analysis method was used to identify themes from data scripts. Results Four themes emerged that reflected radiation therapists’ perceptions of thermoplastic mask use for head and neck cancer immobilization among patients undergoing radiotherapy. Emerged themes were (1) Perceived benefits and limitations of thermoplastic mask use, (2) Refresher training and supervision requirements for effective use, (3) Proper storage for quality maintenance, and (4) Increased financial support and proper budgeting. Conclusion Participants perceived better patient immobilization with a thermoplastic mask use. However, too often recycling of thermoplastic masks and the long waiting time between thermoplastic mask preparation and treatment delivery limits their effective use. For efficient use of thermoplastic masks, there is a need for Radiation therapists’ refresher training and proper supervision, improving the storage system and increasing financial support for procuring new thermoplastic masks.